Politeness in Language and Speech Events in War Situations: Analysis of Abu Ubaidah's Speech - Said, Uswah Mujahidah Rasuna; Arsyad, Hairuddin; Haidar, Alfan; Al Farisi, Mohamad Zaka (Fakultas Ilmu Pendidikan dan Humaniora (FIPH), Universitas Muhammadiyah Semarang, 2024)
Through an analytical study of Abu Ubaidah's speech in a war situation between Hamas-Israel, this qualitative descriptive research explores the elements of Geoffrey Leech's politeness maxims and Dell Hymes' speech events in a war situation. Speech analysis consists of looking for aspects of politeness in the form of maxims of wisdom, maxims of generosity, maxims of praise, maxims of humility, maxims of agreement, and maxims of sympathy. This research found three maxims used in Abu Ubaidah's speech, namely the maxims of praise, humility, and sympathy. This can be seen from Abu Ubaidah's speech by showing the application of these three maxims, such as showing respect, recognition, and sympathy for Allah, the fighters, and the Palestinian people. Analysis was also carried out to look for speech events in settings and scenes, participants, and ends in Abu Ubaidah's speech. The theory of Abu Ubaidah's speech events in the Hamas-Israel conflict includes three main factors: setting and scene involve the location and time of the speech amid intensive attacks in Gaza. Participants include Abu Ubaidah, the al-Qassam Brigades, the Palestinian community, the enemy, and the international community. And ends, which include several main objectives depending on the context of the intended speech partner.